Foix–Chavany Marie syndrome-A rare entity - Dr.M.Deep Tejesh; Dr. Uma M Anand Kumar; Dr.Saranya Masilamani; Dr.Avula Sasidhar Reddy, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Foix–Chavany Marie syndrome (FCMS), is a rare cortical type of pseudobulbar palsy that results in paralysis of orofaciopharyngeal muscles, wwhilethe autonomic, involuntary, and reflexive functions of the above muscles are preserved. Here we present a case of 65-year-old right-handed male patient presented with sudden inability to speak and swallow, or move the tongue, along with difficulty in chewing. While his verbal and reading comprehension were intact, and he communicated through writing and gestures. Neurological examination showed preserved pupillary and corneal reflexes, normal extraocular movements, and loss of voluntary facial and tongue motor control. Early recognition and comprehensive management, including supportive therapy and addressing underlying conditions, are paramount for optimising patient outcomes.